Autoimmune encephalitis in COVID-19 patients: a systematic review of case reports and case series - Xue, Hua; Zeng, Li; He, Hongxian; Xu, Dongxun; Ren, Kaixin (Frontiers in Neurology, 2023)
Background There is mounting evidence suggesting that autoimmune encephalitis (AE) can be observed as a neurological complication in patients with COVID-19. This review aimed to summarize the clinical manifestations, types, and outcomes of COVID-19-associated AE. Methods A systematic search was conducted in the PubMed, Embase, and Web of Science databases to identify case reports and case series related to COVID-19-associated AE from 1 January 2020 to 31 March 2023. After a thorough screening and evaluation, irrelevant articles were excluded. Relevant information concerning types, clinical manifestations, and outcomes was extracted and synthesized. Results A total of 37 studies, comprising 34 case reports and 3 case series, were included in this review. Among the 42 COVID-19-associated AE patients, 21 (50%) cases were classified as an unknown antibodies (Ab) type of COVID-19-associated AE, 10 (23.80%) cases as anti-N-methyl-D-aspartate (NMDA) encephalitis, 4 (9.5%) cases as limbic encephalitis, and 3 (7.1%) cases as anti-myelin-oligodendrocyte-glycoprotein encephalitis, along with other rare types of AE. Disturbance of consciousness, seizures, and psychiatric symptoms were identified as the main clinical manifestations of COVID-19-associated AE. While the symptoms of AE displayed variation, most patients achieved full recovery although a few experienced residual symptoms of neurological damage. Conclusion This systematic review comprehensively describes the characteristics of COVID-19-associated AE. The main type of COVID-19-associated AE identified in this study is an unknown Ab type of COVID-19-associated AE. Despite the potentially life-threatening risks of COVID-19-associated AE, the majority of patients survived, with some patients reporting residual neurological symptoms.